Global supply chain network design and Asian analysis with material-based carbon emissions and tax. (November 2017) - Urata, Tomoyuki; Yamada, Tetsuo; Itsubo, Norihiro; Inoue, Masato
Highlights: An Asian LCI database can be adopted for a global supply chain network design. The total costs and the material-based CO2 emissions by each part are minimized. In higher Carbon tax, both of the proposed design and the emissions payments can be adopted. Abstract: Global warming has become a serious problem. Global supply chain networks in Asia should reduce not only CO2 emissions but also the fixed opening costs for factories/routes as well as the cost of transportation and procurement. Life cycle assessment (LCA) quantitatively estimates and visualizes the CO2 emissions for each part based on their component materials produced on a country by country basis using a life cycle inventory (LCI) database. In general, in order to reduce both of the CO2 emissions and the costs, supply chain planners should make the decision to switch the suppliers of component parts with higher CO2 emissions but lower procurement costs from emerging countries and/or with lower CO2 emissions but higher procurement costs from developed countries. In addition, the European Union (EU) approaches to reducing CO2 emissions through the introduction of emissions tax and trading. This study proposes a design method of an Asian global supply chain network that minimizes the costs under targeted material-based CO2 emissions reduction ratios, and determines the suppliers and factory locations that satisfy demands for low-carbon material supply, through the adoption of the Asian LCI database. Based on this result, a sensitivity analysis is conducted by changing emission prices for reducing the costs and the carbon emissions, and the difference between the supply chain networks comprising of either two and three different Asian countries is compared.